1995
DOI: 10.1002/1097-4679(199511)51:6<831::aid-jclp2270510616>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The effects of description clarity and disorder type on MMPI-2 fake-bad validity indices

Abstract: Simulation research indicates that the MMPI‐2 validity scales easily detect faked‐bad profiles that follow vague, but not specific, instructions. The present study compared the fake‐bad validity scales (i.e., F, F‐Back, F‐K, Fake‐Bad Scale, critical items, and O‐S scales) for differences among one authentic and four simulation (fake‐bad) groups. The simulation groups differed according to the type of disorder simulated (neurotic or psychotic) and the clarity of the behavioral descriptions they received (clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A cutoff score of 20, originally offered by Lees-Haley (1991) resulted in slightly reduced specificity of 85%, though an increased sensitivity of 95%. In contrast, using a cutoff score of 25, as Cramer (1995) suggested, resulted in a lower sensitivity of 81% but relatively high specificity of 95%. Although Lees-Haley (1992) has reported different cutoff scores for males and females, we found no significant differences between men and women across groups on the FBS, t(113) ¼ 0.45, p > .60.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A cutoff score of 20, originally offered by Lees-Haley (1991) resulted in slightly reduced specificity of 85%, though an increased sensitivity of 95%. In contrast, using a cutoff score of 25, as Cramer (1995) suggested, resulted in a lower sensitivity of 81% but relatively high specificity of 95%. Although Lees-Haley (1992) has reported different cutoff scores for males and females, we found no significant differences between men and women across groups on the FBS, t(113) ¼ 0.45, p > .60.…”
Section: Resultsmentioning
confidence: 95%
“…For women, the cut score resulted in a comparable number of malingerers (74%) and controls (92%) being correctly classified. Similarly, Cramer (1995) found that simulators had significantly higher scores on the FBS than authentic patients. A cut score of greater than or equal to 26 was used.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…3. The MMPI-II is the second edition of the Minnesota Muliphasic Personality Inventory; an assessment tool widely used in forensic, clinical and research settings (Cramer, 1995). The MMPI-II is at once a self-report measure and a personality measure.…”
Section: Appendix Imentioning
confidence: 99%
“…These MMPI-2 results are quite similar to those previously reported for the original MMPI. More recent MMPI-2 faking-bad studies with adults (Bagby, Nicholson, Buis, & Bacchiochi, 2000;Cramer, 1995;Lim & Butcher, 1996) also suggest that the F and Fb Scales and the F-K index are the best ways to discriminate persons faking bad from those completing the MMPI-2 with standard instructions.…”
mentioning
confidence: 96%